2018
DOI: 10.1002/jmv.25049
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response to hepatitis B vaccine in HIV‐exposed infants in Malawi and correlation with HBV infection acquisition

Abstract: The aim of this study was to assess the immune response to HBV vaccine in HIV-exposed infants and to correlate it to HBV infection acquisition. Protective anti-HBs levels (>10 mIU/mL) were found in 54/58 (93.2%) infants at 6 months, 126/144 (87.5%) at 12 months and 141/176 (80.1%) children at 24 months. HBV infection (seven children were HBsAg + at Month 24) occurred also in the presence of levels above 10 mIU/mL. Our findings indicate limited impact of HIV exposure on anti-HBV immune response, but suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…21 Decline in immunity from vaccination has been reported from Malawi and South Africa in adolescence leading to an increased risk of acquisition of HBV infection because of sexual activity or injecting drug use. 2,51 Vaccine failures also have been reported as a result of development of escape mutants. 51 The anti-HDV prevalence (4.6%) amongst HBsAg-positive patients was lower than that reported in 1985-1986 from the northern part of Botswana where it had a higher (23% -69%) prevalence in the population at that time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Decline in immunity from vaccination has been reported from Malawi and South Africa in adolescence leading to an increased risk of acquisition of HBV infection because of sexual activity or injecting drug use. 2,51 Vaccine failures also have been reported as a result of development of escape mutants. 51 The anti-HDV prevalence (4.6%) amongst HBsAg-positive patients was lower than that reported in 1985-1986 from the northern part of Botswana where it had a higher (23% -69%) prevalence in the population at that time.…”
Section: Discussionmentioning
confidence: 99%
“…2,51 Vaccine failures also have been reported as a result of development of escape mutants. 51 The anti-HDV prevalence (4.6%) amongst HBsAg-positive patients was lower than that reported in 1985-1986 from the northern part of Botswana where it had a higher (23% -69%) prevalence in the population at that time. 3,22 In patients with liver disease in Africa, anti-HDV prevalence rates of 1% -66.7% have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The median anti-HBs titer in children was 174 mIU/mL [Q1, Q3: 70, 457] which was higher than both the thresholds for protective immunity (>10 mIU/mL), and adequate protective immunity (>100mIU/mL). In Malawi, a retrospective longitudinal study was conducted to assess immune response to HBV vaccine in children exposed to HIV, who had been vaccinated at 6, 10, and 14 weeks of age and to investigate the correlation between not receiving the HBV primary vaccine dose at birth and HBV infection acquisition [8]. Results from the study reported protective (�10mIU/ mL) anti-HBs levels in 54/58 (93.2%) children at 6 months, 126/144 (87.5%) at 12 months, and 141/176 (80.1%) children at 24 months [8].…”
Section: Plos Onementioning
confidence: 99%
“…In Malawi, a retrospective longitudinal study was conducted to assess immune response to HBV vaccine in children exposed to HIV, who had been vaccinated at 6, 10, and 14 weeks of age and to investigate the correlation between not receiving the HBV primary vaccine dose at birth and HBV infection acquisition [8]. Results from the study reported protective (�10mIU/ mL) anti-HBs levels in 54/58 (93.2%) children at 6 months, 126/144 (87.5%) at 12 months, and 141/176 (80.1%) children at 24 months [8]. These results indicated a limited impact of HIV exposure on HBV vaccine response despite the children not receiving the HBV vaccine birth dose.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation